Beyond Opium: A Hexa-Helix Multi-Stakeholder CollaborationModel for Agricultural Transformation in Afghanistan - Adi Susetyo (Records Management System Journal, 2025)
This study examines Afghanistan's agricultural transformation after Taliban's 2022 nationwide opium ban, which cut poppy cultivation by 67% but distrupted milions of livelihoods. The ban, aligned with international and religious standards, highlighted systemic weaknesses such as fragile markets, poor infrastructure, and weak institutional support for alternatives. The research evaluates the Hexa-Helix collaboration model which engaging government, academia, industry, civil society, media and international actors as a governance framework for sustainable rural development in post-conflict settings. Using a systematic literature review and comparative analysis of Thailand's succesful Royal Project Foundation Programme, the study identifies key barriers in Afghanistan: fragmented stakeholder engagement, donor-driven policies, and lack of local governance. Drawing lessons from Colombia and Myanmar, it proposes a reconfigured development governance emphasizing horizontal collaboration, local ownership, and institutional resilience. This approach offers a practical pathway to transform Afghanistan's rural economy beyond opium cultivation, providing valuable insights for peacebuilding and sustainable development efforts regionally and globally.